Manufacturing method of composite hollow fiber membrane
By employing a coating nozzle with a tapered and parallel derivation portion, the method addresses the challenges of non-uniform film thickness and substrate deformation in composite hollow fiber membrane production, resulting in a stable and uniformly coated membrane with enhanced properties.
Patent Information
- Application Number
- JP2021001207
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-17
- Filing Date
- 2021-01-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2041-01-07
AI Technical Summary
Existing methods for manufacturing composite hollow fiber membranes face issues with uniform film thickness and deformation of the hollow fiber substrate due to deviations in the nozzle central axis and vibrations in production equipment.
The method involves using a coating nozzle with a tapered portion and a parallel derivation portion, where the inner diameter of the parallel derivation portion is set to have a ratio of 1 or more with the outer diameter of the hollow fiber substrate, to stabilize the coating process and ensure uniform film thickness.
This configuration reduces deviations between the nozzle and substrate central axes, prevents substrate deformation, and achieves a stable, uniformly thick coating layer with improved process passing ability and fluid permeability.
Smart Images

Figure 0007647105000003 
Figure 0007647105000001 
Figure 0007647105000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a composite hollow fiber membrane. [Background technology]
[0002] A composite hollow fiber membrane in which a separation functional layer is formed on a support is known as a hollow fiber membrane for separating a desired component from a mixed fluid of multiple gases, liquids, etc. One of the manufacturing techniques for the composite hollow fiber membrane is a lamination method in which a polymer solution is coated on a substrate serving as a support, and then the coating layer is fixed and fixed by phase separation or the like to form a separation functional layer on the support.
[0003] As a coating method in the lamination method, a method has been disclosed in which a support is introduced into a nozzle that stores a coating solution that is the raw material for the coating layer, and the coating solution is coated onto the outer surface of the support (Patent Documents 1 and 2). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2004-314059 A [Patent Document 2] JP 2019-107577 A Summary of the Invention [Problem to be solved by the invention]
[0005] As described in Patent Document 1, the use of a coating nozzle made of elastic resin is effective in preventing fiber breakage, but there is a problem in that the thickness uniformity in the circumferential direction and the fiber axis direction decreases due to misalignment between the central axis of the nozzle and the central axis of the hollow fiber substrate, and fluctuations in the fiber path caused by vibrations of the production equipment. In addition, when the hollow fiber substrate passes through the nozzle, the pressure of the fluid inside the nozzle increases, compressing the hollow fiber substrate in the radial direction and causing deformation, which can increase the thickness of the coating layer and decrease the thickness uniformity in the fiber axis direction.
[0006] The present invention provides a method for producing a composite hollow fiber membrane that reduces coating defects caused by deformation of a hollow fiber substrate or fluctuations in the fiber path, can form a uniform coating layer stably over a long period of time, and can reduce the membrane thickness. [Means for solving the problem]
[0007] As a result of investigations, the inventors have found that it is possible to solve both the problems of uniformity in the coating layer thickness and thinning by providing a tapered section and an outlet parallel section at the outlet side of the coating nozzle and by setting the inner diameter of the outlet parallel section so as to satisfy an appropriate relationship with the outer diameter of the hollow fiber substrate.
[0008] That is, the problem in the present invention is mainly solved by any one of the following configurations. (1) A method for producing a composite hollow fiber membrane, comprising passing a hollow fiber substrate through a coating nozzle storing a membrane-forming solution to coat the periphery of the hollow fiber substrate with the membrane-forming solution, wherein the coating nozzle includes a tapered portion and an outlet parallel portion in a cross section parallel to the axial direction of the hollow fiber substrate, the outlet parallel portion constitutes a portion that leads the hollow fiber substrate out of the coating nozzle system, and the ratio B / A of an inner diameter A of the outlet parallel portion to an average outer diameter B of the hollow fiber substrate is 1 or more. (2) A method for producing a composite hollow fiber membrane, comprising passing a hollow fiber substrate through a coating nozzle storing a polymer solution to coat the periphery of the hollow fiber substrate with the polymer solution, wherein the coating nozzle includes a tapered portion and an outlet parallel portion in a cross section parallel to the axial direction of the hollow fiber substrate, the outlet parallel portion constitutes a portion that leads the hollow fiber substrate out of the coating nozzle system, and the ratio B / A of an inner diameter A of the outlet parallel portion to an average outer diameter B of the hollow fiber substrate is 1 or more. Effect of the Invention
[0009] According to the present invention, by providing an outlet parallel section in the coating nozzle, it is possible to suppress fluctuations in the fiber path and perform stable coating for a long period of time, and by setting the inner diameter of the outlet parallel section to satisfy an appropriate relationship with the outer diameter of the hollow fiber substrate, the misalignment of the central axes of the hollow fiber substrate and the coating nozzle is reduced, thereby providing a composite hollow fiber membrane suitable for a separation membrane with excellent thickness uniformity of the separation functional layer formed by coating. [Brief description of the drawings]
[0010] [Figure 1] FIG. 2 is a schematic diagram showing an example of a coating nozzle used in one embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] In the method for producing a composite hollow fiber membrane of the present invention, a hollow fiber substrate is passed through a coating nozzle storing a membrane-forming solution such as a polymer solution to coat the periphery of the hollow fiber substrate with the membrane-forming solution. In this way, a coating layer is formed on the hollow fiber substrate, and the coating layer is fixed and fixed by phase separation or the like, thereby forming a composite hollow fiber membrane having a separation function layer on the hollow fiber substrate. In the following, an embodiment in which a polymer solution is used as a membrane-forming stock solution and the composite hollow fiber membrane is obtained by layer separation will be described in detail, but instead of such an embodiment, a reactive resin precursor solution such as a polyamic acid or a polymerizable monomer solution may be used, and the solution may be coated on the hollow fiber substrate in the same manner as in the case of using a polymer solution, and a cyclization reaction, crosslinking reaction, polymerization reaction, or the like may be allowed to proceed to obtain a composite hollow fiber membrane.
[0012] <Polymer solution> In the present invention, a polymer solution is a precursor of a coating layer that has been given fluidity in order to form a coating layer that will serve as a separation functional layer on a substrate, and is not particularly limited, but is mainly composed of a polymer compound and a solvent.
[0013] The polymer compound must be one that can be dissolved in a solvent, and examples thereof include polyolefins such as polypropylene and polyethylene, and polyesters such as polyethylene terephthalate.Further examples include cellulose-based materials such as cellulose acetate, cellulose acetate propionate, cellulose propionate, cellulose butyrate, regenerated cellulose, or mixtures thereof, polysulfone, polyethersulfone, polyvinylidene fluoride, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polyaramid, polyamide, polymethylmethacrylate, polyphenylene oxide, polyphenylene sulfide, polyetheretherketone, epoxy resins, and phenolic resins.These resins may be used alone or in combination.
[0014] The solvent must be one that dissolves the polymer compound, and may be one type or a combination of multiple types. Any solvent that dissolves the polymer may be used as the solvent for the polymer solution. For example, various solvents may be used, such as aprotic polar solvents such as dimethylformamide, diethylformamide, dimethylacetamide, diethylacetamide, dimethylsulfoxide, N-methyl-2-pyrrolidone, and γ-butyrolactone, alcohols such as methanol and ethanol, tetrahydrofuran, chloroform, and dichloromethane.
[0015] The viscosity of the polymer solution is preferably 1 to 500 Pa·s. The higher the viscosity of the polymer solution, the more susceptible it is to the squeeze film thickness effect and the higher the uniformity of the coating film thickness in the circumferential direction, so the viscosity of the polymer solution is preferably 1 Pa·s or more, and more preferably 20 Pa·s or more. On the other hand, if the viscosity is too high, it becomes difficult to adjust and deliver the polymer solution, so the viscosity of the polymer solution is preferably 500 Pa·s or less, and more preferably 300 Pa·s or less. The viscosity is measured in accordance with JIS Z 8803:2011 10 (Method of measuring viscosity using a cone-plate type rotational viscometer) at 25°C and a shear rate of 1 sec using a rotational viscometer (MCR301, manufactured by Anton-Paar). -1Measured at.
[0016] The polymer solution may contain various additives for the purpose of improving the film-forming property or improving the film properties, as long as the properties are not significantly impaired. The various additives are not particularly limited as long as they meet the above-mentioned purpose, but a non-solvent is preferable for the purpose of producing a porous material using phase separation. It is preferable to select a non-solvent that is miscible with the above-mentioned solvent from the viewpoint of removing the solvent from the coating layer.
[0017] <Hollow fiber substrate> The shape of the hollow fiber substrate in the present invention (hereinafter, sometimes referred to as substrate) is not limited, and any conventionally known substrate can be selected as long as it has a hollow fiber or tubular shape. The material of the substrate is not particularly limited, but is preferably selected from conventionally known substrates. An example is a tube made of a fiber structure such as a woven fabric, knitted fabric, braided fabric, or nonwoven fabric, such as polysulfone, polyethersulfone, polyacrylonitrile, polyvinyl alcohol, cellulose acetate, polyethylene, polypropylene, or polyvinylidene fluoride. It is also preferable to use a substrate made of an inorganic material, such as an alumina or zirconia tube, carbon fiber, silicon carbide fiber, or a fiber structure thereof. When the substrate is an inorganic material, it has excellent chemical resistance, and when a polymer solution is coated, deformation of the hollow fiber substrate due to the solvent contained in the polymer solution is suppressed, and a coating film with excellent thickness uniformity can be obtained.
[0018] The substrate may be non-porous or porous, but is preferably porous. When the substrate is porous, the adhesion between the substrate and the coating membrane is good and the tensile strength is improved, resulting in excellent processability. In addition, the substrate is preferably porous because the permeation resistance is small and the fluid permeability of the finally obtained composite hollow fiber membrane is increased.
[0019] The physical properties of the substrate are not particularly limited, but from the viewpoint of film thickness uniformity, the tensile modulus in the axial direction is preferably in the range of 1 to 100 GPa. If the substrate is deformed by compressive stress when passing through the coating nozzle, the film thickness uniformity decreases, so the tensile modulus is preferably 1 GPa or more from the viewpoint of suppressing deformation of the substrate. That is, if the tensile modulus is 1 GPa or more, the deformation of the substrate due to the pressure inside the coating nozzle can be suppressed, and the film thickness uniformity can be improved, so that a coating film with excellent quality can be obtained. On the other hand, the lower the tensile modulus of the substrate, the more flexible the substrate is, and the more stable the coating can be for a long time by suppressing breakage, so that the tensile modulus is preferably 100 GPa or less, and more preferably 50 GPa or less. The tensile modulus is measured according to JIS L 1013:2010 (chemical fiber filament yarn test method) 8.9 A method.
[0020] <Coating nozzle> 〔shape〕 The coating nozzle used in the present invention may be, for example, as shown in Fig. 1, a nozzle body 31 and an outlet pipe 32 which form a polymer solution reservoir 13 therein. In the coating nozzle shown in Fig. 1, an opening which serves as a polymer solution supply section 11 and an opening which serves as a hollow fiber substrate introduction section 12 are formed in the nozzle body 31, and an outlet pipe 32 is connected to the downstream side in the running direction of the hollow fiber substrate 1. The outlet pipe 32 is composed of a tapered section 14 whose diameter decreases toward the downstream side in the running direction of the hollow fiber substrate 1, and an outlet parallel section 15 which follows the tapered section and leads the hollow fiber substrate 1 out of the coating nozzle 3 system.
[0021] The shape of the polymer solution storage section 13 is not particularly limited as long as it has the function of filling the inside of the nozzle body 31 and the outlet pipe 32 with the polymer solution, and the cross-sectional shape perpendicular to the axial direction of the substrate can be arbitrarily selected from a circle, a polygon, etc. The external shape is not particularly limited, and can be arbitrarily selected from a cone, a cylinder, a prismatic shape, etc.
[0022] The opening that becomes the hollow fiber substrate inlet portion 12 is not particularly limited as long as it has the function of guiding the substrate to the polymer solution reservoir portion 13, and the cross-sectional shape perpendicular to the axial direction of the substrate can be arbitrarily selected, such as circular or polygonal. The cross-sectional shape can be arbitrarily selected according to the state of the substrate, but it is preferable that the cross-sectional shape is similar to the outer shape of the substrate in cross-section. In other words, when the outer shape of the substrate in cross-section is circular, it is preferable that the cross-sectional shape of the opening is also circular.
[0023] In addition to the function of applying the polymer solution to the substrate, the tapered portion 14 exerts a throttling film thickness effect by narrowing its cross-sectional area toward the outlet parallel portion. That is, according to the principle of fluid lubrication in fluid mechanics, when a lubricant is flowed between two surfaces and the distance between the two surfaces narrows along the flow direction of the lubricant, a lubricant film pressure is generated in the lubricant in a direction perpendicular to the flow, and the lubricant is spread in the width direction. This is called a throttling film pressure effect (squeezing effect). As a result, the separation functional layer obtained using a coating nozzle having a tapered portion has improved film thickness uniformity. The larger the angle of the tapered portion 14, the smaller the shear force that the substrate receives from the polymer solution, preventing cutting of the substrate and improving process passability. On the other hand, the smaller the angle of the tapered portion 14, the smaller the deviation of the central axis between the substrate and the coating nozzle. As a result, a membrane with excellent film thickness uniformity and good quality stability can be obtained, and the fluid permeability of the composite hollow fiber membrane finally obtained can also be improved. From the above viewpoints, the angle of the tapered portion 14 is preferably 2° to 40° with respect to the lead-out parallel portion, and more preferably 5° to 25° from the viewpoint of achieving a balanced improvement in processability and film thickness uniformity.
[0024] The lead-out parallel portion 15 plays a role in regulating the position of the substrate when the substrate is led out from the coating nozzle. The longer the length of the lead-out parallel portion 15 along the axial direction of the substrate, the higher the film thickness uniformity in the circumferential direction of the substrate. Therefore, the length of the lead-out parallel portion 15 along the axial direction of the substrate is preferably 0.1 mm or more, more preferably 1 mm or more. On the other hand, if the lead-out parallel portion 15 is too long, the shear force that the substrate receives from the polymer solution when the substrate passes through becomes large, and there is a concern that the substrate may be cut. Therefore, the length of the lead-out parallel portion 15 along the axial direction of the substrate is preferably 30 mm or less, more preferably 20 mm or less. In particular, when the viscosity of the polymer solution at 25°C is 30 Pa·s or more, it is more preferable that the length of the lead-out parallel portion 15 along the axial direction of the substrate is 1 mm or more and 5 mm or less, since the film thickness uniformity and process passability are extremely excellent.
[0025] In the present invention, the inner diameter of the outlet parallel portion 15 is set according to the outer diameter of the hollow fiber substrate used. That is, the ratio B / A of the inner diameter A of the outlet parallel portion 15 to the average outer diameter B of the hollow fiber substrate 1 is set to be 1 or more. By satisfying this relationship, the inner diameter A of the outlet parallel portion 15 can be made thin while improving the thickness uniformity of the separation membrane formed by coating. That is, when the B / A ratio is 1 or more, the clearance between the nozzle and the hollow fiber substrate is very small, being only the width of the outlet parallel portion due to the substrate, so that the deviation of the central axis between the substrate and the coating nozzle is reduced. As a result, a membrane with good quality stability that is thin yet has excellent thickness uniformity can be obtained, and the fluid permeability of the composite hollow fiber membrane finally obtained can be improved.
[0026] Here, the inner diameter A of the lead-out parallel section 15 is an inner diameter calculated by observing a cross section cut perpendicular to the axial direction of the substrate at a position where the axial length of the substrate in the lead-out parallel section 15 is divided into two equal parts with a scanning electron microscope, fitting an ellipse to the void portion present inside the cross section, and calculating the inner diameter from the major axis and minor axis of the ellipse as (major axis + minor axis) / 2. The average outer diameter B of the substrate is an average outer diameter calculated by observing the cross section of the substrate in 100 mm increments in the axial direction for 1 m of the substrate with a scanning electron microscope, fitting an ellipse to each cross section, and calculating the outer diameter from the major axis and minor axis of the ellipse as (major axis + minor axis) / 2.
[0027] The smaller the B / A ratio, the easier it is for the substrate to pass through the outlet parallel section, so the B / A ratio is preferably 1.5 or less, and more preferably 1.3 or less.
[0028] The polymer solution supply unit 11 is not particularly limited as long as it has a function of supplying the polymer solution to the storage unit 13 of the coating nozzle. For example, a conventionally known one can be used from the viewpoint of connection with a supply line, but it is preferable that the cross-sectional shape is circular from the viewpoint of ease of processing and connection.
[0029] [Material] In the coating nozzle, the materials of the polymer solution storage section 13, the hollow fiber substrate introduction section 12, and the polymer solution supply section 11 are not particularly limited, and examples thereof include resins such as polyethylene and polypropylene, metals such as stainless steel, etc. The materials of these sections may be the same as those of the outlet parallel section, and are preferably selected in consideration of chemical resistance, formability, mechanical strength, etc.
[0030] On the other hand, if the outlet parallel portion 15 is made of a soft material, the outlet parallel portion will be expanded by the pressure generated in the polymer solution present inside the nozzle, which will prevent the substrate from being cut or clogged. Also, even if the outer diameter of the substrate fluctuates greatly, the substrate will easily pass through the outlet parallel portion. Therefore, the Martens hardness of the inner surface of the outlet parallel portion 15 is set to 5 N / mm 2 It is preferable that the resistance is less than 5N / mm 2The following conditions are preferable because they can suppress breakage of the substrate due to the outer diameter fluctuation of the substrate: 3N / mm 2 On the other hand, if the Martens hardness of the inner surface of the lead-out parallel portion 15 is large, the deformation of the lead-out parallel portion is suppressed, and the clearance between the substrate and the lead-out parallel portion is easily maintained. Therefore, the Martens hardness is preferably 0.3 N / mm 2 Therefore, the material constituting the inner surface of the lead-out parallel portion has a Martens hardness of 0.3 to 5 N / mm 2 It is preferable to appropriately select the range.
[0031] The Martens hardness defined here is calculated from the relationship between the test force and indentation depth during the indentation process in the evaluation of micro-range indentation hardness corresponding to material parameters (Annex A) in ISO14577-1:2015 (instrumented indentation hardness), and is an index of hardness that includes both plastic and elastic deformation. The higher the Martens hardness value obtained by this method, the harder the material is. Martens hardness is measured using a nanoindenter or a microhardness tester. Specifically, the maximum test load and indentation depth curve when the indentation load of the indenter is increased is obtained, and the value calculated using the following formula is used. A triangular pyramid indenter with an angle of 115° is used for the measurement. HM = F / As(h) = F / (26.43 × h 2 )
[0032] Here, HM is the Martens hardness [N / mm 2 ], F is the maximum test load [N], As(h) is the surface area of the indenter at depth h [mm 2 ], and h indicates the indentation depth [mm].
[0033] The Martens hardness of the inner surface of the coating nozzle is measured by forming two cross sections perpendicular to the axial direction of the substrate, cutting out the parallel part of the coating nozzle so that the thickness between the cross sections is 0.1 mm, and then bonding and fixing it to a silicon substrate so that one of the two cross sections formed by the sample is on the bottom, and performing microhardness measurement. The microhardness measurement point is the side of the sample cross section where the substrate passes through, which is lower than 1 / 2 of the thickness forming the parallel part. However, the part where the microhardness measurement is performed is selected to have an area 10 times or more larger than the area of the indentation, and the indentation test force is 0.1 mN and the indentation depth is within 10 μm. After measuring at any 10 points, the arithmetic average of the data of 8 points excluding the maximum and minimum values is adopted.
[0034] Specific examples of materials constituting the lead-out parallel portion include rubber and thermoplastic elastomers. Examples of rubber include natural rubber (NR), synthetic natural rubber (isoprene rubber) (IR), butadiene rubber (BR), styrene-butadiene rubber (SBR), butyl rubber (IIR), nitrile rubber (NBR), ethylene-propylene rubber (EP), chloroprene rubber (CR), acrylic rubber (ACM, ANM), chlorosulfonated polyethylene rubber (CSM), urethane rubber (PUR, U), silicone rubber (Si, Q, VMQ, SR), fluororubber (FKM, FEPM, FFKM), ethylene-vinyl acetate rubber (EVA), epichlorohydrin rubber (CO, ECO), and polysulfide rubber (T). Examples of thermoplastic elastomers include polystyrene-based, olefin / alkene-based, polyvinyl chloride-based, polyurethane-based, polyester-based, and polyamide-based elastomers. From the viewpoints of solvent resistance to the solvent contained in the polymer solution and mechanical strength, synthetic natural rubber, butadiene rubber, styrene-butadiene rubber, butyl rubber, ethylene-propylene rubber or silicone rubber is preferred. EXAMPLES
[0035] Preferred examples of the present invention will be described below, but the present invention is not limited to these examples.
[0036] [Thickness uniformity] In order to evaluate the thickness uniformity of the obtained coating film, the maximum average thickness and minimum average thickness of the coating film were measured, and the ratio of maximum average thickness / minimum average thickness was used as an index of thickness uniformity. The ratio was 1.2 or less, which was very excellent uniformity, 1.2 or more and 1.5 or less, which was excellent uniformity, 1.5 or more and 3.0 or less, which was good uniformity, and anything greater than 3.0 was unsuitable. Here, the maximum average thickness and minimum average thickness were calculated as follows. First, the coating film was cut in 100 mm increments while suppressing deformation, and the film cross section was observed with a scanning electron microscope. An ellipse was fitted to the substrate part of each cross section by the least squares method, and the film thickness was measured by scanning from the contact point to the outside of the substrate in a direction perpendicular to the tangent to the obtained ellipse. Then, the maximum and minimum values in the observed film cross sections were calculated, and the arithmetic mean value of the maximum values and the arithmetic mean value of the minimum values in all the observed cross sections were taken as the maximum average thickness and the minimum average thickness, respectively.
[0037] [Example 1] A two-component curing silicone rubber was poured into a mold for a coating nozzle, heated in a hot air dryer to cause a crosslinking reaction, and then cooled and removed from the mold to produce a coating nozzle made of silicone rubber. In the produced coating nozzle, the outlet parallel part 15 was hollow tubular, with an inner diameter A of 4300 μm and an axial length of the substrate of 2 mm. The Martens hardness of the inner surface of the outlet parallel part was 0.5 N / mm 2 The angle of the tapered portion 14 based on the lead-out parallel portion was 30°.
[0038] Using the coating nozzle thus prepared, a coating layer was formed on a substrate made of porous alumina (hollow shape, tensile modulus of elasticity 7 GPa, outer diameter 5000±100 μm, average outer diameter B 5000 μm). At this time, the B / A ratio was 1.16. The detailed conditions for forming the coating layer were as follows:
[0039] A polymer solution consisting of polyacrylonitrile / dimethyl sulfoxide (DMSO) (mass ratio 30 / 70) was supplied to the coating nozzle, and the substrate was transported to coat the polymer solution on the substrate. After that, a coating layer was formed on the substrate through a solidification and drying process.
[0040] The ratio of maximum average thickness to minimum average thickness of the coating layer was 1.14, which showed excellent thickness uniformity and processability. In particular, the processability was so excellent that no breakage of the substrate was observed even after 50 m of continuous operation.
[0041] [Example 2] Except for changing the inner diameter A of the outlet parallel part of the coating nozzle to 4900 μm, a coating layer was formed in the same manner as in Example 1. At this time, the B / A ratio was 1.02.
[0042] The ratio of maximum average thickness to minimum average thickness of the coating layer was 1.31, indicating excellent thickness uniformity. In particular, the processability was excellent, with no breakage of the substrate observed even after 50 m of continuous operation.
[0043] [Example 3] Except for changing the inner diameter A of the outlet parallel part of the coating nozzle to 3400 μm, a coating layer was formed in the same manner as in Example 1. At this time, the B / A ratio was 1.47.
[0044] The ratio of maximum average thickness to minimum average thickness of the coating layer was 1.09, indicating excellent thickness uniformity and good processability, although the substrate broke once during 50 m of continuous operation.
[0045] [ Comparative Example 1 ] A coating layer was formed in the same manner as in Example 1, except that the length of the outlet parallel part of the coating nozzle was changed to 0.7 mm.
[0046] The ratio of maximum average thickness to minimum average thickness of the coating layer was 1.46, indicating excellent thickness uniformity, and the processability was excellent, with no breakage of the substrate observed even after 50 m of continuous operation.
[0047] [Example 4 ] A coating layer was formed in the same manner as in Example 1, except that the length of the outlet parallel part of the coating nozzle was changed to 28 mm.
[0048] The ratio of maximum average thickness to minimum average thickness of the obtained coating layer was 1.05, which showed excellent thickness uniformity. In addition, the processability was also excellent, with no breakage of the substrate observed even after continuous operation for 50 m.
[0049] [ Comparative Example 2 ] A coating layer was formed in the same manner as in Example 1, except that the length of the outlet parallel part of the coating nozzle was changed to 35 mm.
[0050] The ratio of maximum average thickness to minimum average thickness of the obtained coating layer was 1.08, which showed excellent thickness uniformity. In addition, although the substrate broke twice during 50 m of continuous operation, the process was satisfactory.
[0051] [Example 5 ] A coating nozzle was produced in the same manner as in Example 1, in which the outlet parallel part 15 was hollow tubular, the inner diameter A was 260 μm, and the length in the axial direction of the substrate was 2 mm. The Martens hardness of the inner surface of the outlet parallel part was 0.5 N / mm 2 The angle of the tapered portion 14 based on the lead-out parallel portion was 30°.
[0052] Using the prepared coating nozzle, a coating layer was formed on a porous substrate made of polysulfone (hollow shape, tensile modulus of elasticity 1.5 GPa, outer diameter 300±10 μm, average outer diameter B 300 μm) in the same manner as in Example 1. At this time, the B / A ratio was 1.15.
[0053] The ratio of maximum average thickness to minimum average thickness of the coating layer was 1.41, indicating excellent thickness uniformity, and the processability was excellent, with no breakage of the substrate observed even after 50 m of continuous operation.
[0054] [Example 6 ] A coating nozzle was produced in the same manner as in Example 1, in which the outlet parallel part 15 was hollow tubular, the inner diameter A was 430 μm, and the length in the axial direction of the substrate was 2 mm. The Martens hardness of the inner surface of the outlet parallel part was 0.5 N / mm 2 The angle of the tapered portion 14 based on the lead-out parallel portion was 30°.
[0055] Using the prepared coating nozzle, a coating layer was formed on a porous substrate made of polyethylene (hollow shape, tensile modulus of elasticity 0.7 GPa, outer diameter 500±10 μm, average outer diameter B 500 μm) in the same manner as in Example 1. At this time, the B / A ratio was 1.16.
[0056] The ratio of maximum average thickness to minimum average thickness of the coating layer was 2.27, indicating good thickness uniformity, and the processability was excellent, with no breakage of the substrate observed even after 50 m of continuous operation.
[0057] [Example 7 ] A coating layer was formed in the same manner as in Example 1, except that a substrate made of porous alumina (hollow shape, outer diameter 5000±100 μm, average outer diameter B 5000 μm) in which the porosity was appropriately adjusted to a tensile modulus of 54 GPa was used.
[0058] The ratio of maximum average thickness to minimum average thickness of the obtained coating layer was 1.08, which showed excellent thickness uniformity. In addition, although the substrate broke once during 50 m of continuous operation, the process was satisfactory.
[0059] [Example 8 ] Using the same method as in Example 1, the degree of crosslinking of the silicone rubber was appropriately adjusted, and the Martens hardness of the inner surface of the lead-out parallel part was 6.5 N / mm 2 The coating nozzle was produced. The outlet parallel part was hollow tubular, with an inner diameter A of 4300 μm and a length of 2 mm in the axial direction of the substrate. The angle of the tapered part 14 based on the outlet parallel part was 30°.
[0060] A coating layer was formed on the same substrate as in Example 1 using the prepared coating nozzle.
[0061] The ratio of maximum average thickness to minimum average thickness of the coating layer was 1.10, which showed excellent thickness uniformity. In addition, although the substrate broke once during 50 m of continuous operation, good processability was also demonstrated.
[0062] [Example 9 ] A coating layer was formed in the same manner as in Example 1, except that the angle of the tapered portion of the coating nozzle was changed to 8°.
[0063] The ratio of maximum average thickness to minimum average thickness of the obtained coating layer was 1.03, which showed excellent thickness uniformity. In addition, although the substrate broke once during 50 m of continuous operation, the process was satisfactory.
[0064] [Example 10 ] A coating layer was formed in the same manner as in Example 1, except that the angle of the tapered portion of the coating nozzle was changed to 24°.
[0065] The ratio of maximum average thickness to minimum average thickness of the obtained coating layer was 1.08, which showed excellent thickness uniformity. In addition, the processability was also excellent, with no breakage of the substrate observed even after continuous operation for 50 m.
[0066] [Comparative Example 3 ] Except for using a coating nozzle with an inner diameter A of 5300 μm at the outlet parallel part, a coating layer was formed in the same manner as in Example 1. At this time, the B / A ratio was 0.94.
[0067] Although no breakage of the substrate was observed even after 50 m of continuous operation, the ratio of maximum average film thickness to minimum average film thickness of the coating layer was 3.52, indicating poor film thickness uniformity.
[0068] [Table 1] TIFF0007647105000001.tif223125
[0069] [Table 2] TIFF0007647105000002.tif249125 [Industrial Applicability]
[0070] INDUSTRIAL APPLICABILITY The present invention can be suitably used in the production of a composite hollow fiber membrane used for separating a desired component from a mixed fluid of a plurality of gases and liquids. [Explanation of symbols]
[0071] 1. Hollow fiber substrate 3 Coating nozzle 11 Polymer solution supply section 12 Hollow fiber substrate introduction section 13 Polymer solution storage section 14 Tapered section 15 Lead-out parallel section 16 Inner layer of lead-out parallel section 17 Outer layer of lead-out parallel section 31 Nozzle body 32 Outlet pipe
Claims
1. A method for producing a composite hollow fiber membrane, comprising passing a hollow fiber substrate through a coating nozzle storing a membrane-forming solution to coat the periphery of the hollow fiber substrate with the membrane-forming solution, wherein the coating nozzle includes a tapered portion and an outlet parallel portion in a cross section parallel to the axial direction of the hollow fiber substrate, the outlet parallel portion constitutes a portion that leads the hollow fiber substrate out of a system of the coating nozzle, the length of the outlet parallel portion is 1 to 30 mm, and the ratio B / A of an inner diameter A of the outlet parallel portion to an average outer diameter B of the hollow fiber substrate is 1 or more.
2. A method for producing a composite hollow fiber membrane, comprising passing a hollow fiber substrate through a coating nozzle storing a polymer solution to coat the periphery of the hollow fiber substrate with the polymer solution, wherein the coating nozzle includes a tapered portion and an outlet parallel portion in a cross section parallel to the axial direction of the hollow fiber substrate, the outlet parallel portion constitutes a portion that leads the hollow fiber substrate out of a system of the coating nozzle, the length of the outlet parallel portion is 1 to 30 mm, and the ratio B / A of an inner diameter A of the outlet parallel portion to an average outer diameter B of the hollow fiber substrate is 1 or more.
3. The method for producing a composite hollow fiber membrane according to claim 1 or 2, wherein the hollow fiber substrate has a tensile modulus of elasticity of 1 to 100 GPa.
4. The Martens hardness of the inner surface of the lead-out parallel portion is 5 N / mm 2 The method for producing a composite hollow fiber membrane according to any one of claims 1 to 3, wherein the composite hollow fiber membrane is:
5. The method for producing a composite hollow fiber membrane according to any one of claims 1 to 4, wherein a ratio B / A of an inner diameter A of the outlet parallel portion to an average outer diameter B of the hollow fiber substrate is 1 or more and 1.5 or less.
Citation Information
Patent Citations
A method for preparing a long fiber reinforced hollow fiber membrane
CN102266726A
Preparation method and preparation device for enhanced hollow fiber composite film
CN103007778A
Coating nozzle for hollow fiber membrane and production method of composite hollow fiber membrane using it
JP2004314059A
Hollow fiber membrane module
JP2008080314A
Coating nozzle of fibrous product and manufacturing method of composite fibrous product
JP2019107577A